A Management Information System: A Strategic Solution To Improve Operational Efficiency: An analytical Perspective on the Role of MIS in Enhancing Organizational Performance - Nita Nofa Risma; Mansur Chadi Mursid (JSI: Jurnal Sistem Informasi (E-Journal), 2025)
Management Information Systems (MIS) are an important part of modern organizational management that functions to support the decision-making process, coordination, control, analysis, and visualization of information in a company. This article discusses the main role of MIS in improving operational efficiency and effectiveness of managerial decision-making. In addition to explaining the definition and benefits of MIS, this article also describes three main factors that influence the success of its implementation, namely organizational factors, management factors, and technology factors. These three factors interact with each other and determine the extent to which the system can provide added value to the organization. The discussion also covers how MIS helps organizations, both large and small, respond to dynamic market changes and overcome operational limitations. In the ever-evolving digital era, the use of information technology through MIS allows companies to act more adaptively, competitively, and sustainably. Therefore, a thorough understanding of the concept, supporting factors, and implementation of management information systems is crucial for the overall success of the organization.